Level of stress, factors associated with stress and coping strategies among advanced level students attending tuition classes in a selected educational zone in Sri Lanka - Athukorale, Uthpalee P.; Balasooriya, Naduni A. P.; Jayasinghe, Pradeesha L. S.; Nagawegedara, Pavithri M.; Ranasinghe, Chamini Y.; Perera, Ramani; Goonewardena, Sampatha E. (International Journal Of Community Medicine And Public Health, 2020)
Background: Advanced level is a challenging examination due to the limitation of University entrance opportunities leading to high level of stress. Several issues have affected them irrespective of the stream of study, for which they tend to adapt different coping strategies. Therefore, the objective of this study was to determine the level of stress, factors associated with stress and coping strategies among advanced level (A/L) students attending tuition classes in selected Educational zone, Sri Lanka. Methods: A descriptive cross- sectional study was conducted among 364 A/L students aged between 17-20 years attending a selected tuition class. Self-administered questionnaire was used with 35 item coping strategy check list and DASS-21, both tools were pretested and validated in Sri Lanka. Data was analysed using SPSS 15.0 software. Results: Vastness of the A/L curriculum was a significant stress factor between males and females (p=0.001). Stress of getting lower grades and poor time management were higher among females (p=0.027, p=0.003). Males reported change in sexual habits (p=0.003) and alcohol /cigarette use (p=0.001). Lack of vacation and fear of academic failure were the most common physical and emotional stressors respectively. Seeking advice from a trusted person, being with others, blaming themselves for the situation, engaging in religious activities, listening to music, constantly thinking about the problem and crying to self were common coping strategies adopted by females. Immediate problem solving and consuming alcohol/ drugs were common coping strategies by males. Conclusions: Males had more social and physical stress associated factors whereas females had academic and emotional stressors. Different methods of coping strategies were adopted by males and females.